PHOTOMETRIC CHARACTERIZATION OF A COMMERCIAL DSLR CAMERA FORTHE IMPLEMENTATION OF AN IMAGING LUMINANCE METER - O. U. Preciado; A. Décima; J. B. Barraza (Anales (Asociación Física Argentina), 2021)
In this paper we describe the procedure followed in the photometric characterization of a DSLR camera in order to implement an imaging luminance meter. The first step consisted in the experimental setup of a system to obtain the spectral response curves of the CMOS sensor for its three channels: red (R), green (G) and blue (B). Then, based on the linear combination of the RGB channel curves, we calculated an approximation of the CIE luminous efficiency function, V(λ), for the camera. We then characterized the camera lens which involved measuring its spectral transmittance and evaluating the uniformity of the lens-sensor assembly to compensate for loss of sensitivity at the image periphery(vignetting). Finally, we performed an absolute calibration in luminance and carried out a pilot test to create high dynamic range (HDR) images and luminance maps of a scene. The favourable results of the pilot test augur a successful implementation of the image luminance meter, however, it is necessary to finish with the development of a software for the image processing and to do more tests in order to be able to validate its use in different situations or to establish the restrictions of its use.